Implementasi Quality Assurance Pada Konsep Trilogi di Yayasan Pendidikan Islam Ulul Albab Jember - Siti Junita; Zainuddin Al Haj Zaini; Abd Muhith; Muhammad Faisal A. Ghani (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This research explores the trilogy concept's application in improving student quality and educational standards at the Ulul Albab Islamic Education Foundation. The research method uses a qualitative descriptive approach with case studies, and this research focuses on the quality of teachers, students, and parents. The results show the foundation's commitment to producing students with character through learning activities and extracurricular learning. Increasing teacher quality can be realized through investment in human resources, which increases individual capital. Meanwhile, through parenting activities and home visits, the role of parents in educating children at home is strengthened. A holistic approach involving all relevant parties, full support from the environment, community, and government, and the implementation of quality management and national standards are the keys to improving the quality of Islamic education. The implication is that greater collaborative efforts are needed between all stakeholders to implement effective strategies in improving education quality and increasing educators' competence in educating the next generation.